Proceso de atención de enfermería en gestante epiléptica de 40.6 semanas. - Navas Amaguaya, Johana Salome (2021)
The present clinical case concerns a 40.6-week pregnant woman with epilepsy who attends the emergency service of the Alfredo Noboa Montenegro Hospital accompanied by her mother at 9:00 p.m. on Febrary 16, 2021 for presenting a full-term pregnancy due to FUM plus work of childbirth and history of epilepsy. It is worth mentioning that the patient was referred to the Echeandia Health Center for presenting a seizure for 1 occasion plus labor, where he was administered as paracetamol 10mg plus intravenous hydration. The objective of the case is to apply the nursing care process in epileptic pregnant women that contributes to improving their current health status through the study of clinical history in order to improve their condition. The applied methodology consisted of physical and complementary examinations; In addition, altered functional patterns such as sleep-rest and cognitive were identified. The implemented treatment is composed of: NPO for 4 hours, Mom Score every 15 minutes, AFU control and bleeding every 15 minutes, 0.9% saline solution 1000 ml plus 10 IU of oxytocin pass IV at 120 ml / hr, celtriaxone 1gr IV every 12 hours, removal of urinary catheter, soft diet, among others. During the controls, the patient presented hemodynamic alteration, risk of falls, mild pain at the uterine level without the presence of clots, a patent bladder catheter, a covered, clean and dry surgical wound. The interventions carried out were satisfactory during the patient's admission, improving his health condition.